Chronic fatigue syndromes: real illnesses that people can recover from - Tomas Nordheim Alme; Anna Andreasson; Tarjei Tørre Asprusten; Anne Karen Bakken; Michael BJ Beadsworth; Birgitte Boye; Per Alf Brodal; Elias Myrstad Brodwall; Kjetil Gundro Brurberg; Ingrid Bugge; Trudie Chalder; Reidar Due; et al. (Scandinavian Journal of Primary Health Care)
The ‘Oslo Chronic Fatigue Consortium’ consists of researchers and clinicians who question the current narrative that chronic fatigue syndromes, including post-covid conditions, are incurable diseases. Instead, we propose an alternative view, based on research, which offers more hope to patients. Whilst we regard the symptoms of these conditions as real, we propose that they are more likely to reflect the brain's response to a range of biological, psychological, and social factors, rather than a specific disease process. Possible causes include persistent activation of the neurobiological stress response, accompanied by associated changes in immunological, hormonal, cognitive and behavioural domains. We further propose that the symptoms are more likely to persist if they are perceived as threatening, and all activities that are perceived to worsen them are avoided. We also question the idea that the best way to cope with the illness is by prolonged rest, social isolation, and sensory deprivation.Instead, we propose that recovery is often possible if patients are helped to adopt a less threatening understanding of their symptoms and are supported in a gradual return to normal activities. Finally, we call for a much more open and constructive dialogue about these conditions. This dialogue should include a wider range of views, including those of patients who have recovered from them.